Whats's critical about Critical Theory again? Critical Theory, ethnocentrism, sexism and racism - Farr, Arnold Lorenzo (Perspectivas em Diálogo: Revista de Educação e Sociedade, 2023)
The purpose of the article is to examine some of the weaknesses of critical theory with regard to race and gender, as well as to critique the limitations of critical theory stemming from its ethnocentrism. In it the author argues for a return to the deeper engagement with the breadth of contemporary social, political, and emancipatory theories and movements as seen in the first generation of the Frankfurt School. As a case in point, he shows that Angela Davis' omission from the history of critical theory indicates the degree to which even critical theory is haunted by racism, ethnocentrism, and sexism. These shortcomings of critical theory make it necessary to revisit critical theory once again, carrying forward the provocation made by Nancy Fraser in her essay entitled “What’s Critical About Critical Theory?”. As a result of the argument, the author suggests that a new critical theory, which brings Herbert Marcuse and Angela Davis into contact with other recent theories, would lead to more fruitful forms of critical theory that would help overcome the one-dimensional concerns of traditional critical theory.